2005
DOI: 10.1128/aac.49.3.996-1001.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Damage and Bacterial Load in Assessment of the Efficacy of Simulated Human Treatment-Like Amoxicillin (2,000 Milligrams) Therapy of Experimental Pneumococcal Pneumonia Caused by Strains for Which Amoxicillin MICs Differ

Abstract: An experimental rat pneumonia model using two amoxicillin-susceptible (MICs, <0.015 and 2 g/ml) and two non-amoxicillin-susceptible (MIC, 4 g/ml) Streptococcus pneumoniae strains was developed for testing the efficacy of amoxicillin administered to simulate human serum kinetics after treatment with amoxicillinclavulanate (2,000 and 125 mg, respectively, twice a day, for 2.5 days). The end points for efficacy were reductions in bacterial loads in the lungs and reductions in levels of pulmonary damage. For the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In severe pneumonia, only early antibiotic therapy, administered prior to barrier breakdown, prevented systemic inflammation, development of pleuritis, steatitis and elevated AST levels, which was followed up by restoration of fitness and rescue of mice from fatal outcome. Gracia et al [ 41 ] have shown in S. pneumoniae -infected rats that early and late antibiotic regimens similarly eliminated bacterial burdens whereas only early therapy helped to prevent lung damage. However, the authors started early therapy just 1 h p.i., an important difference to our protocol whereby infected mice already developed pneumonia prior to antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In severe pneumonia, only early antibiotic therapy, administered prior to barrier breakdown, prevented systemic inflammation, development of pleuritis, steatitis and elevated AST levels, which was followed up by restoration of fitness and rescue of mice from fatal outcome. Gracia et al [ 41 ] have shown in S. pneumoniae -infected rats that early and late antibiotic regimens similarly eliminated bacterial burdens whereas only early therapy helped to prevent lung damage. However, the authors started early therapy just 1 h p.i., an important difference to our protocol whereby infected mice already developed pneumonia prior to antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the postmarketing phase, animal models have been used to study pharmacodynamic prediction of efficacy in systemic infections caused by strains with decreased susceptibility using humanized models [34], the relationship of pharmacodynamic parameter values with tissue injury [35], the effects of treatment delay on pharmacodynamics [35], the significance of local (as middle ear fluid) vs. serum pharmacodynamic parameters in local infections (otitis media) [36], pharmacodynamics in mixed local infections (S. pneumoniae þ H. influenzae) [37], the effect of the disease (acute otitis media vs. otitis media with effusion) on pharmacodynamics in middle ear fluid [38], or the effect of concomitant medications as analgesics on the relationship between pharmacodynamic parameters and eradication [39,40].…”
Section: The In-vivo Linkmentioning
confidence: 99%